2011
DOI: 10.1002/pi.3173
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in solid‐state organic lasers

Abstract: Organic solid-state lasers are reviewed, with a special emphasis on works published during the last decade. Referring originally to dyes in solid-state polymeric matrices, organic lasers also include the rich family of organic semiconductors, paced by the rapid development of organic light emitting diodes. Organic lasers are broadly tunable coherent sources are potentially compact, convenient and manufactured at low-costs. In this review, we describe the basic photophysics of the materials used as gain media i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
286
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 347 publications
(297 citation statements)
references
References 192 publications
(343 reference statements)
5
286
0
6
Order By: Relevance
“…Equation (8) reveals that J 0 increases with z. Based on this equation, we discuss the effect of exciton diffusion on the roll-off characteristics depending on X in the linear devices.…”
Section: ½S ãmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation (8) reveals that J 0 increases with z. Based on this equation, we discuss the effect of exciton diffusion on the roll-off characteristics depending on X in the linear devices.…”
Section: ½S ãmentioning
confidence: 99%
“…Exciton-polaron annihilation is the most critical issue to overcome because all polarons have a broad absorption spectrum. [8][9][10][11] In our previous study, we demonstrated high current injection of over 1000 A cm À2 without device breakdown into OLEDs with an unusual device configuration of a small active area (200 Â 200 nm) on a high thermally conductive substrate by application of a short pulse voltage of less than 1 ls. 12,13 However, very serious efficiency roll-off was observed at such high current density.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The second-order solid-state organic distributed feedback laser (DFB) [14,15] represents the next step from passive to active optical refractometric sensors, because the structure incorporates its own source of optical gain and feedback, so that it allows achieving narrow bandwidth output through the process of stimulated emission [16,17]. Although the linewidths achievable by DFB sensors are generally not narrower than those obtained with some of the sensors mentioned, they are simultaneously capable of high sensitivity and a high degree of resolution.…”
Section: -Introductionmentioning
confidence: 99%
“…Tunable visible sources based on nonlinear fibers and frequency conversion recently appeared on the marketplace but are available at a cost comparable with that of dye lasers or OPOs. In pulsed regime, organic solid-state lasers (OSSLs) 10,11 are then very appealing devices which combine the advantages of dye lasers with those of conventional solid-state lasers, with a "low-cost" advantage. Two types of OSSLs can be distinguished: lasers with bulk (≈ cm) dye-doped polymer chips, and thin-film based lasers (which include organic semiconductor lasers 11 ).…”
mentioning
confidence: 99%